Energy and global climate change bridging the sustainable development divide - Cherian, Anilla (John Wiley and Sons, Ltd, 2015)
"This book, is exactly the expansion of the concept of energy access for poor in terms of its linkages with climate change and sustainable development that is the main focus of investigation. In this regard, the argument that is advanced is not whether and how to increase energy access for the poor, or whether and how to improve the prospects for a comprehensive climate change agreement, but instead to ask whether and how energy access for the poor has been factored into the series of key UN led intergovernmental climate change and sustainable development outputs"--Provided by publisher.